Surveying consumer preferences for eco-labeled fruits and vegetables in Euro-Mediterranean alternative food systems - Aminravan, Marzieh; Ahmadi Kaliji, Sina; Mulazzani, Luca; Rota, Cosimo; Camanzi, Luca (Frontiers in Sustainable Food Systems, 2025)
The growing environmental challenges in Mediterranean fruit and vegetables production, including water scarcity, soil degradation, and biodiversity loss, have led to increased interest in alternative food systems as a pathway to sustainable agriculture. However, a significant research gap remains in understanding consumer preferences for eco-labeled fruit and vegetables within these systems, particularly in comparison to conventional supply chains. Short food supply chains emphasize local engagement, transparency, and reduced environmental impact, whereas export-oriented supply chains prioritize large-scale production for global market but face concerns regarding their environmental implications. This study addresses this gap by analyzing the key drivers influencing willingness to pay for eco-labeled fruit and vegetables in short food supply chains and export-oriented supply chains, providing novel insights into consumer decision-making across different supply chain structures. Specifically, it investigates how consumers in these two supply chain systems differ in their attitudes toward eco-labels, focusing on interest in label information, environmental concerns, and trust in certifications. Using data from an online survey conducted in June 2023 in Italy, France, and Greece with a final sample of 1,163 respondents, this study follows a two-step approach. First, one-way analysis of variance is used to assess differences in consumers' attitudes toward eco-labels between supply chains. Second, partial least squares structural equation modeling is used to estimate relationships and identifies key drivers of willingness to pay for eco-labeled fruit and vegetables. The results show that trust in certifications emerges as the strongest predictor of willingness to pay in both supply chains, especially within short food supply chains. Interest in label information also plays a significant role in both contexts, while environmental concerns are more relevant for consumers in export-oriented supply chains. Younger consumers exhibit stronger preferences for eco-labeled fruit and vegetables, while education levels show no significant effect. The analysis highlights the distinct roles of supply chains in shaping consumer preferences. Short food supply chains foster trust through local engagement and transparency, reducing the need for formal certifications, whereas export-oriented supply chains rely more on certifications due to their more industrialized and impersonal nature. These findings contribute to the literature on sustainable food consumption by demonstrating how trust, information, and environmental awareness interact in different supply chain contexts. The study provides practical insights for policymakers and stakeholders to refine certification strategies and improve consumer engagement, ultimately supporting the development of sustainable food systems.